Utilization of Postnatal Care Services among Mothers Residing in Morang District, Nepal - Limbu, Chandrakala; Kuwar, Chanchala; Shrestha, Sapana; Shrestha, Neha; Fyak, Sanjita (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: Post-natal care is regarded as the care provided to the mother and the baby during first six weeks of childbirth. Large proportion of maternal and neonatal deaths occur during postnatal period. The utilization of postnatal care services helps in preventing maternal and neonatal deaths. The study aim to find out the utilization of postnatal care services among postnatal mothers residing in Morang district, Nepal. Methods: A Cross sectional study was undertaken among 256 postnatal mothers residing in Kanepokhari rural municipality, Belbari and Sundarharaincha municipality of Morang district. Multi stage sampling method was used. Ethical approval was obtained from PUSHS- Institutional review committee (Ref no 041—078/079). Face to face interview was done using self developed semi structure questionnaire to collect the data. Descriptive statistics were performed and chi –square was done. Multivariable logistic regression was done Results: Nearly half (47.3%) had utilized the postnatal care services. Very few (6.6%) of the respondents were aware about the importance about the PNC utilization. Most (85.2%) of the respondents were unaware about the government protocol of PNC visit. Educational level, duration of stay at hospital parity, danger sign seen in pregnancy, place of delivery and mode of delivery were associated with having utilization of postnatal services. The primi mothers (95% CI: 1.229-0.403) had higher likelihood of having postnatal care utilization. Conclusions: Nearly half postnatal mothers have utilized the postnatal care services. Awareness programme focusing on government protocol for postnatal services should be done to improve the utilization.